Dediščina SLOfit-a oz. športnovzgojnega kartona - Jurak, Gregor (Šport (Ljubljana), 2017)
We present some important segments of the heritage of the system for monitoring and evaluating physical and motor development of school children, called SLOfit, which is also known under the name of the Sports Educational Chart and earlier even the Physical Educational Chart. This nationwide monitoring has been implemented in all Slovenian schools since 1987. In April every year, nearly all Slovenian primary and secondary school pupils are systematically measured. The measurements include eight motor and three anthropometric measurement tasks. The SLOfit database is one of the largest databases on children%s physical and motor development in the world, encompassing more than 7 million measurements and more than 1 million residents of Slovenia until the present day. Centralised data management and evaluation based on feedback enable children and parents to compare a child%s physical and motor development with that of his/her peers. The system enables researchers to monitor the trends in physical and motor development of the school population, whereas teachers can help themselves with it when planning the learning process. SLOfit data serve as a scientific backbone for most policies related to school physical education and physical activity of children and youth. The data are frequently used for international comparisons, analyses of global trends, analyses of effects of different interventions as well as other types of applied research. Owing to high credibility of the SLOfit data, Slovenia has one of the most effective programmes of school and extra-curricular physical education in the world, which is reflected in the high level of physical activity and physical fitness of children and adolescents compared to the rest of the world.
Keywords: adolescents; anthropometry; antropometrija; children; gibalni razvoj; javno zdravje; mladina; motor development; otroci; physical activity; physical condition; physical development; physical fitness; politika; public health; SLOfit; sport; Sport Educational Chart; šport; športna vzgoja; športnovzgojni karton; telesna dejavnost; telesna pripravljenost; telesni fitnes; telesni razvoj